Asuhan Keperawatan Pada Tn.S Dengan Nyeri Abdomen (Abdominal Pain) Di Ruang Kemuning RSUD Dr. Soeselo Kabupaten Tegal - Nurhidayati Nurhidayati; Tati Karyawati; Muhammad Silahudin (STIKes Ibnu Sina Ajibarang, 2023)
Pain is a phenomenon that is often found in life and is a sign of tissue damage in the body. Pain is a form of discomfort that can be caused by many things. Pain can arise due to the effects of certain diseases or the result of injury. Pain is often considered a sign that something is physiologically disturbed, causing someone to ask for help. Pain is also a serious problem that must be responded to and intervened by providing a sense of security and comfort and even relieving the pain (Fathoni & Cindy, 2019).